2007
DOI: 10.1111/j.1468-2508.2007.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining American Identity in the Twenty-First Century: How Much “There” is There?

Abstract: This study examines whether the increasing ethnic diversity of the United States is changing how the normative content of American identity is defined. It relies on a wide-ranging set of norms to test the claim that an increasingly multicultural America will engender a multicreedal America. In addressing this claim, the study provides an empirical assessment of the "multiple traditions" theory and develops more accurate measures of how Americans view the content of American identity than has typically been inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 33 publications
7
178
1
2
Order By: Relevance
“…Ethnoculturalism and civic republicanism, for the most part, encompass the questions examined in this study but liberalism and incorporationism are also found to influence where, when, and how people draw boundaries of American identity (Schildkraut 2002(Schildkraut , 2007(Schildkraut , 2014. Continuing to expand the measures used to delineate the symbolic boundaries of American identity is important for future research and upcoming waves of the GSS.…”
Section: Discussionmentioning
confidence: 89%
“…Ethnoculturalism and civic republicanism, for the most part, encompass the questions examined in this study but liberalism and incorporationism are also found to influence where, when, and how people draw boundaries of American identity (Schildkraut 2002(Schildkraut , 2007(Schildkraut , 2014. Continuing to expand the measures used to delineate the symbolic boundaries of American identity is important for future research and upcoming waves of the GSS.…”
Section: Discussionmentioning
confidence: 89%
“…Some researchers have addressed assimilation hypotheses by focusing on immigrant groups' attitudes (Schildkraut, 2007;de la Garza et al, 1996;Alba, 2006), but considerable measurement error is associated with attitudinal measures (Zaller, 1992). As a result, the present analysis, based on the reported behavior of the subjects, may have stronger implications given the stronger face validity of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…This set of values are best represented in the contemporary notion of the American Dream which encompasses individualism, equal opportunity, and the idea of "success" (Hochschild 1995;Cullen 2003;Jillson 2004;Ghosh 2008). Schildkraut (2007) has discovered that a "broad range of constitutive norms define being American" thus confirming that "multiple traditions" (Smith 1997) inform…”
Section: Part IImentioning
confidence: 95%
“…The American polity, for instance, routinely identifies itself as a nation of believers in the values of the American Dream (Citrin 1994;Hochschild 1995;Cullen 2003;Jillson 2004;Schildkraut 2007;Ghosh 2008). Most Americans believe that those who work hard should succeed.…”
Section: What Role Does Reasoned Argument Play In Politics? In the Fementioning
confidence: 99%